Is the ultrasound-estimated bladder weight a reliable method for evaluating bladder outlet obstruction? - Almeida, Fernando G. (2011)
OBJECTIVETo evaluate the correlation between ultrasound-estimated bladder weight (UEBW) in patients with different degrees of bladder outlet obstruction (BOO).METHODSWe evaluated 50 consecutive non-neurogenic male patients with lower urinary tract symptoms (LUTS) referred to urodynamic study (UDS). All patients self-answered the International Prostate Score Symptoms (IPSS) questionnaire. After the UDS, the bladder was filled with 150 mL to determine UEBW.Patients with a bladder capacity under 150 mL, a previous history of prostate surgery or pelvic irradiation, an IPSS score <8, a bladder stone or urinary tract infection were excluded.After a pressure-flow study, the Schafer linear passive urethral resistance relation nomogram was plotted to determine the grade of obstruction: Grades I-II/VI were defined as mild obstruction, Grades III-IV/VI as moderate obstruction, and Grades V-VI/VI as severe obstruction.RESULTSThe UEBW was 51.7 +/- 26.9, 54.1 +/- 30.0 and 54.8 +/- 28.2 in patients with mild, moderate and severe BOO, respectively (P = 0.130). The UEBW allowed us to define four groups: (i) UEBW < 35 g; (ii) 35 g <= UEBW < 50 g; (iii) 50 g <= UEBW < 70 g; and (4) UEBW >= 70 g.We did not find any differences in age, prostate weight, IPSS, PVR, cystometric bladder capacity, presence of detrusor overactive and degree of obstruction in the aforementioned groups.CONCLUSIONDespite the fact that some studies have emphasized the value of UEBW as an efficient non-invasive method for evaluating lower urinary tract obstruction, our study suggests that UEBW does not present any individual correlation with LUTS or objective measurements of BOO.